Implementing Andragogy In Indonesian Theological Schools - Sumule, Leonard (Jurnal Jaffray, 2018)
Most Christians inIndonesia, when asked about the term "school" or "Sunday school", they always think that those terms are addressed to childrens education. Even the term "Adult Sunday School", which is a very familiar sound in the ears of Christians inAmerica, is not heard of among the churches inIndonesia. Why? According to the Christians inIndonesia, Sunday School is always intended for children. It is also carried in general education. That is why the term education is always directed to the education of the children or young persons rather than to adult education.It is time that theological schools inIndonesiaunderstand the importance of andragogy for adult Christian education. InIndonesia, adults do not like the idea of Sunday school or school because they think Sunday school or school is for children and it is beneath their dignity.Â  However, utilizing the andragogical methods described in this paper, adult can learn in a dignified manner.Â  Instead of being lectured what to know as children would be, adults should realize that each one is an integral part of the learning process. Through respectful participation, each adult can learn through discovery as well as contribute insight to others.Â